Orexin A-Mediated Modulation of Reproductive Activities in Testis of Normal and Cryptorchid Dogs: Possible Model for Studying Relationships Between Energy Metabolism and Reproductive Control - Assisi, Loredana; Pelagalli, Alessandra; Squillacioti, Caterina; Liguori, Giovanna; Annunziata, Chiara; Mirabella, Nicola (Frontiers in Endocrinology, 2019)
Orexin A (OxA) is a neuropeptide produced in the lateral hypothalamus that performs pleiotropic functions in different tissues, including involvement in energy homeostasis and reproductive neuroendocrine functions. The role of OxA is particularly important given the well-studied relationships between physiological mechanisms controlling energy balance and reproduction. The enzyme P450 aromatase (ARO) helps convert androgens to estrogens and has roles in steroidogenesis, spermatogenesis, and energy metabolism in several organs. The goal of this study was thus to investigate the role of OxA in ARO activity and the effects of this regulation on reproductive homeostasis in male gonads from healthy and cryptorchid dogs. The cryptorchidism is a specific condition characterized by altered reproductive and metabolic activities, the latter of which emerge from impaired glycolysis. OxA helps to stimulate testosterone (T) synthesis in the dog testis. We aimed to investigate OxA-mediated modulation of 17β-estradiol (17β-E) synthesis, ARO expression and metabolic indicators in testis of normal and cryptorchid dogs. Our results indicate putative effects of OxA on estrogen biosynthesis and ARO activity based on western blotting analysis and immunohistochemistry for ARO detection and in vitro tests. OxA triggered decrease in estrogen production and ARO activity inhibition; reduced ARO activity thus prevented the conversion of T to estrogens and increasing OxA-mediated synthesis of T. Furthermore, we characterized some metabolic and oxidative modulations in normal and cryptorchid dog's testis. The steroidogenic regulation by OxA and its modulation of ARO activity led us to hypothesize that OxA is a potential therapeutic target in pathological conditions associated with steroidogenic alterations and OxA possible involvement in metabolic processes in the male gonad.